Optimum network reconfiguration and DGs sizing with allocation simultaneously by using Particle Swarm Optimization (PSO) - Mohd Nasir, Mohamad Na'im; Shahrin, Nur Mazura; Sulaima, Mohamad Fani; Jali, Mohd Hafiz; Baharom, Mohamad Faizal (Science Publishing Corporation Inc, 2014)
This paper presents three stages of methodology. The first stage is to identify the switching operation for radial network configuration while observe the power losses and the voltage profile without Distributed Generation (DG). The second stage is based on previous paper which is feeder reconfiguration for loss reduction with DGs. The last stage is sizing and allocation DGs at buses with low voltage profile resulted from the first stage to improve the power losses and voltage profile also comparing the result with the second stage. The objective of this method proposed is to show that allocation of DGs simultaneously based on low voltage profile can improve network power losses and improvement of voltage profile. The result shows that improvement on network power losses is 54.92% from Distribution Network Reconfiguration (DNR) method. All three stages were tested on standards IEEE 33 bus system by using Particle Swarm Optimization (PSO) technique in MATLAB software. This method proved that improvement of power losses and voltage profile by switching and DGs allocation method.